TWO DESIGNS OF THE ELECTROMECHANICAL BRAKE EMBEDDED INTO AN ASYNCHRONOUS MOTOR - V. V. Solencov; V. V. Brel (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2016)
The significance of the braking devices is increasing due to the intensification of manufacturing, increase in the moving masses, speeds of movement and frequency of braking. During a short time period the braking device needs to convert a significant amount of mechanical energy into heat energy and transfer it into the environment without compromising the operability of both devices and machines in general. For electric actuators braking a normally closed mechanical brake is frequently used. When disconnecting the motor from the network the brake friction surfaces are closed and prevent rotation, and when the motor is switched on, they are opens under the action of the electromagnet, electro-hydraulic pusher, special electric motor, mechanical or pneumatic device. In the case of joint implementation of the asynchronous motor and the mechanical brake, the drive of quick stop is more compact and convenient. Such devices are further called asynchronous motors with electromechanical braking systems henceforth. The large number of requirements as well as different conditions of operation cause a large variety of designs of such motors. One of the major shortcomings of the functioning of well-known design is the periodic wear of the friction linings and the need for frequent replacement of them. The solution to this problem is the use of asynchronous motor with recessed combo braking device. However, for some mechanisms that do not require a smooth stop of the motor shaft and that have a speed of rotation of the motor shaft less than 1500 rpm, more simple and cheap solution would be the use of an electromechanical braking device with an air gap compensation. Due to wear of the friction linings the air gap of the electromagnet increases. Due to the compensation of the air gap of the electromagnet these devices make it possible to rub the material of the friction lining longer. The current designs of the electromechanical braking device with compensation of the air gap are quite bulky and complicated to be manufactured. Therefore, the authors developed, experimentally investigated and implemented two new, simple and cheap designs of electromechanical braking device with compensation of the air gap.